MODUL BIOLOGI PADA MATERI KONSEP DASAR SEL MELALUI PEMBELAJARAN BIBLE BASED INTEGRATION UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI - LANGI, JERRY CHRISNY MARLA; BUNGKANG, YUSUF; SIALLAGAN, JOHNSON (Jurnal Ilmu Pendidikan Indonesia, 2019)
The aim of the biology module is on cell basic concepts by using Bible-based integration to improve learning outcomes of students of Class XI IPA Kalam Kudus Christian Jayapura. The results of this study are: There is an increase in learning achievement of class XI students using the Bible Based Integration learning module with n-Gain RPP-1 0.61, n-Gain RPP-2 0.67, n-Gain RPP-3 0.74. The average n-Gain RPP is 0.67 with the medium category.